Post-Quantum Migration in the Financial Sector: A Systematic Review of Readiness, Risks, and Transition Frameworks - Hillary Muzenda; Belinda Ndlovu (Journal of Information System and Informatics, 2026)
Quantum computing threatens the classical cryptographic systems underpinning financial infrastructure, exposing payment platforms, interbank networks, and digital services to Harvest-Now-Decrypt-Later (HNDL) risks. This study systematically reviews quantum threats and post-quantum cryptographic readiness in the financial sector to assess preparedness, identify implementation challenges, and synthesize migration pathways aligned with emerging standards. A PRISMA-guided review of 17 peer-reviewed studies published between 2020 and 2025 was conducted, examining quantum threat models, post-quantum cryptographic schemes, quantum key distribution architectures, and sector-specific deployment barriers. The review finds that lattice-based schemes, especially CRYSTALS-Kyber and CRYSTALS-Dilithium, are the leading candidates for financial adoption, while hybrid cryptographic approaches offer the most feasible transition strategy. However, the current evidence base is predominantly simulation-driven, with limited real-world deployment and validation. The study provides a sector-specific synthesis of quantum threats, post-quantum readiness, and migration pathways in financial systems, and advances an integrated readiness and migration framework based on cross-study thematic analysis.